Sociological Foundations in the Development of the Arabic Language Curriculum - Isop Syafei; Ade Arip Ardiansyah; Dadan Nugraha (UIN Sunan Gunung Djati Bandung, 2025)
This study discusses the sociological foundations in the development of the Arabic language curriculum as a response to social dynamics, community needs, and global challenges that influence the educational process. The Arabic language curriculum cannot be separated from the socio-cultural context in which learning takes place, as language is an integral part of community life. The purpose of this study is to identify and analyze the sociological dimensions that play a role in shaping an Arabic curriculum that is relevant and adaptive to the changing times. This research employs a qualitative approach using a literature review method, examining various references on educational sociology theories, language policies, and curriculum practices within Islamic educational environments. Data collection was conducted through documentation of primary and secondary sources and analyzed using a descriptive-analytical approach. The results show that the development of a sociologically-based Arabic curriculum must consider factors such as students’ social backgrounds, intercultural communication needs, and the role of Arabic in fostering global Islamic solidarity. Such a curriculum can serve as a bridge between local values and global demands, promoting learning that is contextual, participatory, and inclusive in accordance with the learners’ social realities.